Mutant p53 in Cancer Progression and Targeted Therapies - Zhu, Gaoyang; Pan, Chaoyun; Bei, Jin-Xin; Li, Bo; Liang, Chen; Xu, Yang; Fu, Xuemei (Frontiers in Oncology, 2020)
TP53 is the most frequently mutated tumor suppressor gene in human cancer. The majority of mutations of p53 are missense mutations, leading to the expression of the full length p53 mutant proteins. Mutant p53 (Mutp53) proteins not only lose wild-type p53-dependent tumor suppressive functions, but also frequently acquire oncogenic gain-of-functions (GOF) that promote tumorigenesis. In this review, we summarize the recent advances in our understanding of the oncogenic GOF of mutp53 and the potential therapies targeting mutp53 in human cancers. In particular, we discuss the promising drugs that are currently under clinical trials as well as the emerging therapeutic strategies, including CRISPR/Cas9 based genome edition of mutant TP53 allele, small peptide mediated restoration of wild-type p53 function, and immunotherapies that directly eliminate mutp53 expressing tumor cells.